M MANAJEMEN KEGAWATAN FASE INTRA-HOSPITAL PADA PASIEN DENGAN COVID-19 - M. Sobirin Mohtar; Muhammad Reza Apriandi (Journal of Nursing Invention, 2020)
Emergency cases that often occur in hospitals which have recently become the world's hottest news are the corona virus disease (Covid-19). Actions taken in the emergency room must be in accordance with the guidelines. As part of emergency health management in the emergency room, a nurse needs to think about strategies that can be done to minimize the death rate of patients infected with the Corona virus and save patients without having to be infected. This study aims to determine the emergency management of the intra-hospital phase in covid 19 patients. The research method used is literature review through searches for articles and journals using accessible databases, namely Google Scholar, Free Full PDF, PubMed,.SchiHub.and.Portal.Garuda. It is known from 7 Journal Literatures in emergency management of COVID-19 patients in the emergency room that it must be done as much as possible to minimize the number of deaths that occur, carry out various management of primary surveys & secondary surveys, especially in patients with infection emergency, handling of patients with heart attacks due to infection. by paying attention to the level of PPE. This is important for a professional nurse to pay attention to many things in providing emergency nursing care to Covid-19 patients.